Modeling and Testing of Magnetic Speed Controlled Submersible Robot for Hydroponic Production - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
This research presents a control method and design steps for a meso-scale robot with a magnetic flagellum actuator for the early diagnosis, prevention, on-site and quick evaluation of the diseases that may occur in the roots of the plants in the hydroponic fields. A commonly known technique for root assessment is to take the plant from its environment and check for diseases and put it back to its environment, which can cause stress on the plant and can lead the death of it. Having these evaluations inside the plants environment will not put any stress on the plants and will allow researchers to take multiple samples without harming the roots. The design of the robot includes three motors equipped with neodymium magnets mounted to the end of their shafts, which were radially located around the flagellum. The flagellum is made from silicone and ferrofluidic liquid which consists billions of iron molecules. Rotation of radially located motors with permanent magnets attached to the tips of their shaft creates a controllable magnetic field that influences the iron molecules inside the flagellum and can change the orientation of it. The issues related with the root disease can be diagnosed with the help of a ccd camera located in the front of the robot and with the processing of that data with computer vision techniques. © 2019 IEEE.
Keywords: biomimetic robotics; flagellum; Meso-Scale Robotics; swimming robots